PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA PENJUMLAHAN DAN PENGURANGAN SAMPAI DENGAN 20 BERBASIS BENDA KONKRET SISWA KELAS 1 SD - Dwi Apriliana; Nadiya Salsa Billa; Rika Aulia Hummairoh; Siti Nurul Husna; Dwi Novita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a mathematics learning module for addition and subtraction up to 20 based on concrete objects and to determine its feasibility and effectiveness for first grade students. The Research and Development (R&D) method used follows the Borg and Gall model which is simplified into six stages: needs analysis, design, development, validation, revision, and limited trials. The research subjects involved 25 first grade students and teachers at SDN 105378 SEMENTARA. Data were collected through observation, interviews, questionnaires, and tests. The results showed that the developed module was very feasible and effective to use. The classical completion rate reached 84%, where 21 students obtained a score of ≥ 76 which exceeded the Minimum Completion Criteria (KKM) of 75. In addition, as many as 88% of students showed an attitude of cooperation and confidence during learning activities using concrete objects. It can be concluded that this concrete object-based module successfully improved students' conceptual understanding and learning outcomes by bridging abstract mathematical operations through real experiences.